43‐4: Self‐Shading with Optically‐ and Thermally‐Switchable Liquid Crystals. Issue 1 (30th May 2018) - Oh, Seung-Won; kim, Sang-Hyeok; Baek, Jong-Min; Yoon, Tae-Hoon
Abstract : Self‐shading by optical or thermal switching between transparent and opaque states is achieved by liquid crystals doped with push‐pull azobenzene and can be used for energy‐saving smart windows. The self‐shading light shutter is transparent during cool weather or under weak sunlight, which could save the energy used for heating and lighting, and can be switched from the transparent to opaque states during warm weather or under strong sunlight, saving energy used for cooling.